A Case Report of "Propofol Frenzy": Anesthetic Considerations for a Severe Propofol-Induced Neuroexcitation Reaction. Issue 3 (14th March 2022) - Panchamia, Jason K.; Amundson, Adam W.; Demirci, Onur; Braksick, Sherri A.; Wijdicks, Eelco F.
Abstract : Propofol "frenzy" is considered a severe propofol-induced neuroexcitatory reaction involving nonepileptic spells of extremity thrashing, marked agitation, irregular eye movements, and impaired consciousness. Patients with propofol neuroexcitation present unique challenges for anesthesia providers due to underrecognition, lack of diagnostic tests, and differentiating from other comparable disorders that require medications that can exacerbate symptoms. We present a case of a healthy young patient whose postoperative course was complicated by propofol frenzy and functional limb paralysis following hip surgery with a spinal anesthetic and propofol sedation. This case highlights anesthesia considerations for propofol frenzy and discusses dexmedetomidine as a promising modality for prompt management.